Preclinical studies of automated radiolabeled microcarriers for radiosynovectomy of inflammatory joint disease. (December 2022) - Postovalova, Alisa S.; Karpov, Timofey E.; Akhmetova, Darya R.; Rodimova, Svetlana A.; Kuznetsova, Daria S.; Antuganov, Dmitrii O.; Sysoev, Dmitry S.; Muslimov, Albert R.; Stanzhevsky, Andrei A.; Zyuzin, Mikhail V.; Timin, Alexander S.
Highlights: The automated process of microcarriers radiolabeling was developed for radiosynovectomy of inflammatory joint disease. Developed microparticles possess high biocompatibility in vitro and in vivo, can be effectively loaded with 188Re therapeutic radionuclide. Applied 188Re-labeled carriers can significantly reduce knee joint swelling and inflammation in synovium and cartilage recovery, decreasing the levels of inflammatory factors (TNF-α, IL-6, and IL-1b). Abstract: The broad implementation of therapeutic loaded nano- and microcarriers has led to significant progress in the treatment of inflammatory joint diseases, especially in the case of radiological synovectomy using β-emitting radioisotope labeled carriers. However, the lack of automated procedures for radiolabeling of these carriers seriously limits their further translation into clinical practice. Here, we develop the automated process of microcarriers radiolabeling for radiosynovectomy of inflammatory joint disease (synovitis in an arthritis rat model). The fabricated polymeric microparticles (MPs) possess high biocompatibility in vitro and in vivo, can be effectively loaded with 188 Re therapeutic radionuclide (∼ 97, 98%), and exhibit good radiochemical stability (up to 95%). In vivo biodistribution demonstrates the accumulation of intra-articular injected 188 Re-MPs in the knee joint (> 96%ID/g for 7 d) without radiation exposure to other healthy organs. It has been shown that the applied radiosynovectomy with 188 Re-MPs can significantly reduce knee joint swelling (knee joint with synovitis ∼ 1.8 ± 0.1 cm versus treated knee joint ∼ 1.1 ± 0.1 cm) and leads to the improvement of inflammation in synovium and cartilage recovery, decreasing the levels of inflammatory factors (TNF-α, IL-6, and IL-1b). Although there are very limited clinical trials on radiosynovectomy of inflammatory joint disease, this study is a step towards implementation of the developed automated labeling procedure for the real application of radiosynovectomy with 188 Re in clinics.